Pemikiran Filosofis tentang Kehidupan dan Peran Pendidikan Islam dalam Sistem Pendidikan Nasional: Philosophical Thoughts on Life and the Role of Islamic Education in the National Education System - Hanifah Nurul; Difa Rahma Melati; Miftah Hidayaturrahmah; Ahla Nisrina (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study aims to examine the philosophical perspective on the meaning of life and the role of Islamic education within the national education system. The research employs a qualitative approach using a library research method, through the analysis of philosophical literature, the thoughts of Islamic and Western scholars, and educational policies in Indonesia. The findings indicate that, from an Islamic perspective, human beings have dual roles as servants of God and vicegerents (khalifah) on earth, which require an educational system that balances intellectual, moral, and spiritual dimensions. Islamic education plays a strategic role in shaping insan kamil, a complete human being characterized by faith, knowledge, and noble character. Within the national education system, Islamic education has been integrated through institutions such as pesantren, madrasah, and Islamic schools, although challenges remain in the integration of Islamic values. Therefore, strengthening a holistic and integrative educational approach is necessary to produce a generation that is both morally grounded and capable of facing contemporary challenges